Low-Dose Linezolid for Treatment of Patients With Multidrug-Resistant Tuberculosis. (5th October 2022) - Mase, Anjeli; Lowenthal, Phil; True, Lisa; Henry, Leslie; Barry, Pennan; Flood, Jennifer
Abstract: Background: Linezolid has been prioritized for treating multidrug-resistant tuberculosis (MDR TB), but toxicity limits its use. We report treatment outcomes for MDR TB patients in California who received standard-dose linezolid vs those who switched to low-dose. Methods: We include culture-positive MDR TB cases treated with linezolid and receiving California MDR TB Service consultation during 2009–2016. Demographic, clinical, and laboratory data are analyzed using univariate analysis to compare patients who received linezolid of different dosing strategies. Analysis end points are linezolid treatment duration (measure of tolerability), treatment success (completion or cure), and adverse events (AEs). Results: Sixty-nine of 194 (36%) MDR TB patients met inclusion criteria. While all patients began linezolid treatment at 600 mg daily, 39 (57%) continued at this dosage (standard-dose), and 30 (43%) switched to 300 mg daily (29%) or intermittent dosing (14%) (low dose). Patients on standard-dose linezolid were treated for 240 days, compared with 535 for those on low-dose ( P < .0001). Sixty-three patients (91%) achieved treatment success, 2 (2.9%) died, 1 (1.5%) failed treatment, 1 (1.5%) stopped treatment due to side effects, and 2 (2.9%) were lost or moved. Treatment success was higher ( P = .03) in the low-dose group. Sixty-two patients experienced ≥1 hematologic (71%) or neurologic (65%) AE. Those on low-dose linezolid experienced significantly ( P = .03) fewer AEs per linezolid-month after switching (0.32 vs 0.10). Conclusions: Patients who switched to low dose tolerated linezolid longer with better treatment outcomes and fewer recurring AEs.